2012
DOI: 10.3233/wor-2012-0197-462
|View full text |Cite
|
Sign up to set email alerts
|

Heavy physical work under time pressure: the garbage collection service- a case study

Abstract: The increased generation of garbage has become a problem in large cities, with greater demand for collection services. The collector is subjected to high workload. This study describes the work in garbage collection service, highlighting the requirements of time, resulting in physical and psychosocial demands to collectors. Ergonomic Work Analysis (EWA) -a method focused on the study of work in real situations was used. Initially, technical visits, global observations and unstructured interviews with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…one hand) elevated the risk of persistent MSDs in the WCs and this result agreed with published studies that reported an association between the increased risk of MSDs and poor working postures, quick motion, and continuous bending or twisting while carrying or lifting heavy objects [4], [8], [9], [37].…”
Section: Factors Related To the Risk Of Persistent Msdssupporting
confidence: 91%
“…one hand) elevated the risk of persistent MSDs in the WCs and this result agreed with published studies that reported an association between the increased risk of MSDs and poor working postures, quick motion, and continuous bending or twisting while carrying or lifting heavy objects [4], [8], [9], [37].…”
Section: Factors Related To the Risk Of Persistent Msdssupporting
confidence: 91%